2018
DOI: 10.1370/afm.2314
|View full text |Cite
|
Sign up to set email alerts
|

Access to Primary Care for Persons Recently Released From Prison

Abstract: We aimed to determine if a history of recent imprisonment affects access to primary care. Using patient roles, we telephoned to request an initial appointment with all family physicians (n = 339) who were accepting new patients in British Columbia, Canada. We sequentially assigned patient scenarios: male or female recently released from prison; male or female control. Controls were 1.98 (95% CI, 1.59-2.46) times as likely to be offered an appointment compared with persons recently released from prison, with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…A recent study in BC showed that people are more likely to be refused by a family physician if they disclose a history of incarceration. 11 In addition, women incarcerated in Ontario identified health literacy and knowledge of services as barriers to accessing health care inside prison and in the community. 26 A peer health mentor may help to navigate services and to identify specific services and practitioners who will not discriminate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in BC showed that people are more likely to be refused by a family physician if they disclose a history of incarceration. 11 In addition, women incarcerated in Ontario identified health literacy and knowledge of services as barriers to accessing health care inside prison and in the community. 26 A peer health mentor may help to navigate services and to identify specific services and practitioners who will not discriminate.…”
Section: Discussionmentioning
confidence: 99%
“…Given increased emergency department visits, it is also possible that people recently released from prison had clinical indications for readmission, but either were not offered readmission or were offered but did not accept the offer of readmission. This is concerning, as it could indicate discrimination on the basis of legal status [19,[34][35][36] or on the basis of characteristics that are overrepresented in this population such as low socioeconomic status or mental illness. If people were choosing to not follow medical advice when they are acutely ill, this would also be problematic; deciding to not be admitted to hospital could reflect competing priorities such as the need to use substances, considering the high prevalence of substance use disorders and admissions for substance-use related conditions [14-18, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…on.ca. the time of prison release [19,22]. As health status and health care quality and access may vary substantially in prison and after release, we stratified people who had experienced imprisonment by whether they were discharged from hospital to prison or to the community into groups called people in prison and people recently released from prison.…”
Section: Exposure Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in which investigators phoned family physicians' offices in British Columbia requesting an initial appointment finds that patients identifying as having recently been discharged from prison were half as likely to get an appointment. 5 In an academic health care system in Cleveland, Margolius et al find that access to appointments is lower for patients of physicians with less time scheduled in the office, but is not associated with larger panel sizes. 6 Shires et al assess the willingness of Midwestern US primary care clinicians to provide routine care to transgender patients, and identify factors associated with this willingness.…”
mentioning
confidence: 99%